Modified dispersive liquid‐phase microextraction based on sequential injection solidified floating organic drop combined with HPLC for the determination of phenobarbital and phenytoin. Issue 2 (11th December 2017) - Amiri Pebdani, Arezou; Dadfarnia, Shayessteh; Haji Shabani, Ali Mohammad; Khodadoust, Saeid; Talebianpoor, Mohammad Sharif
Abstract: A modified dispersive liquid phase microextraction based on sequential injection solidified floating organic drop was developed for simultaneous separation/preconcentration of trace amounts of phenobarbital and phenytoin. The important factors affecting on the extraction recovery including pH, the volume of extraction solvent, ionic strength, and the number of injections were investigated and optimized by Box–Behnken design and desirability function. Under the optimum experimental conditions, the calibration graph was linear in the concentration range of 1.0–300.0 μg/L ( r 2 = 0.997) for phenobarbital and 2.0–400.0 μg/L ( r 2 = 0.996) for phenytoin. The limit of detection and limit of quantification were 0.35 and 1.2 μg/L for phenobarbital and 0.65 and 2.2 μg/L for phenytoin, respectively. The relative standard deviation for six replicate determinations at 10 μg/L was 3.3 and 4.1% for phenobarbital and phenytoin, respectively. The developed method was successfully applied to the determination of phenobarbital and phenytoin in urine and plasma samples.